Sex Differences in Depression Caused by Early Life Stress and Related Mechanisms - An, Xianquan; Guo, Wanxu; Wu, Huiying; Fu, Xiying; Li, Ming; Zhang, Yizhi; Li, Yanlin; Cui, Ranji; Yang, Wei; Zhang, Zhuo; Zhao, Guoqing (Frontiers in Neuroscience, 2022)
Depression is a common psychiatric disease caused by various factors, manifesting with continuous low spirits with its precise mechanism being unclear. Early life stress (ELS) is receiving more attention as a possible cause of depression. Many studies have focused on the mechanism underlying how ELS leading to changes in sex hormones, neurotransmitters, HPA axis function, and epigenetics. The adverse effects of ELS on adulthood are mainly dependent on the time window when stress occurs, sex and the developmental stage when evaluating the impacts. Therefore, with regard to the exact sex differences of adult depression, we found that ELS could lead to sex-differentiated depression through multiple mechanisms including 5-HT, sex hormone, HPA axis, and epigenetics.